(untitled) (Teaching and Learning Inquiry, 2013)
In recent years, as pressures for accountability have increased in higher education, some members of the Scholarship of Teaching and Learning (SoTL) community may worry that the inquiry-based, improvement-focused practices they advocate could be put at risk by easy-to-administer, one-size-fits-all forms of assessment, quality assurance, and administrative control. But while acknowledging both real and perceived tensions between these two movements, we also examine some of the ways and settings in which they are converging, featuring a number of international examples in which external quality and assessment mandates have been employed to support SoTL-like work. We look, too, at the roles that scholars of teaching and learning can play as mediators and brokers between the two movements, helping to translate accountability requirements into opportunities for improvement. In short we argue that these two movements present opportunities for each other. SoTL can contribute to what is, or should be, the central goal of accountability: ensuring and improving the quality of student learning. The accountability movement, for its part, can provide a new context for integrating and valuing SoTL as a force for positive change on campuses and beyond. Taken together, the two approaches can make meaningful contributions to higher learning today. The paper concludes with recommendations to the SoTL community for building bridges between the two movements.